2014
DOI: 10.1093/heapol/czu026
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of patient charges at primary care facilities in Kenya: implications of low adherence to user fee policy for users and facility revenue

Abstract: With user fees now seen as a major hindrance to universal health coverage, many countries have introduced fee reduction or elimination policies, but there is growing evidence that adherence to reduced fees is often highly imperfect. In 2004, Kenya adopted a reduced and uniform user fee policy providing fee exemptions to many groups. We present data on user fee implementation, revenue and expenditure from a nationally representative survey of Kenyan primary health facilities. Data were collected from 248 random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
2
22
1
Order By: Relevance
“…Costs due to medicine have been shown to reduce adherence to medication and demand for health services by patients with NCDs . Past studies conducted in LMICs have however shown that social health insurance schemes do not comprehensively cover the costs for medicines and that OOP costs, which are majorly contributed by medicines, are a hindrance to attainment of universal health coverage in many low resource settings . Indeed, any reductions or removal of medicine costs is likely to increase access to DM health care services, but additional resources will be required to cover any concomitant increase in service utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Costs due to medicine have been shown to reduce adherence to medication and demand for health services by patients with NCDs . Past studies conducted in LMICs have however shown that social health insurance schemes do not comprehensively cover the costs for medicines and that OOP costs, which are majorly contributed by medicines, are a hindrance to attainment of universal health coverage in many low resource settings . Indeed, any reductions or removal of medicine costs is likely to increase access to DM health care services, but additional resources will be required to cover any concomitant increase in service utilization.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Though Kenya has implemented a policy to decrease user fees, 36 especially for the poorest Kenyans, there is a lack of adherence to this policy. 37 And there are still many indirect costs associated with seeking care from a health facility such as the cost of transportation, food, and foregone work. 35 Home case management by well-trained well-supplied CHWs may be one way to expand access to care to this population.…”
Section: Discussionmentioning
confidence: 99%
“…; Opwora et al. ), health care utilization (The Demographic and Health Surveys Program ; Etiaba et al. ), provider behavior during the clinical consultation (Stange et al.…”
Section: Summary Of Sampling Methods For Patient Exit Interviewsmentioning
confidence: 99%
“…, patients' out-of-pocket expenditures (Peabody et al 2010;Chimbindi et al 2015;Opwora et al 2015), health care utilization (The Demographic and Health Surveys Program 2015;Etiaba et al 2015), provider behavior during the clinical consultation (Stange et al 1998;Ostroff, Li, and Shelley 2014), and patients' knowledge about their condition (Senarath et al 2007;Anya, Hydara, and Jaiteh 2008;Israel-Ballard, Waithaka, and Greiner 2014). A number of standardized patient exit questionnaires have been developed for use by researchers, including the EUROPEP instrument (Wensing 2006), the RAND Patient Satisfaction Questionnaire (RAND Health 2015), the Patient Experiences Questionnaire (Steine, Finset, and Laerum 2001), and the patient exit questionnaires that form part of the Demographic and Health Surveys (DHS) Program's Service Provision Assessments (The Demographic and Health Surveys Program 2015).…”
mentioning
confidence: 99%